Quality of life and affective well-being in middle-aged and older people with chronic medical illnesses: a cross-sectional population based study. - Anna Wikman; Jane Wardle; Andrew Steptoe (PLoS ONE)
Background There has been considerable research into the impact of chronic illness on health-related quality of life. However, few studies have assessed the impact of different chronic conditions on general quality of life (QOL). The objective of this paper was to compare general (rather than health-related) QOL and affective well-being in middle aged and older people across eight chronic illnesses. Methods and findings This population-based, cross-sectional study involved 11,523 individuals aged 50 years and older, taking part in wave 1 of the English Longitudinal Study of Ageing. General QOL was assessed using the CASP-19, happiness was evaluated using two items drawn from the GHQ-12, and depression was measured with the CES-D. Analysis of covariance and logistic regression, adjusting for age, gender and wealth, were performed. General QOL was most impaired in people with stroke (mean 37.56, CI 36.73-38.39), and least in those reporting cancer (mean 41.78, CI 41.12-42.44, respectively), compared with no illness (mean 44.15, CI 43.92-44.39). Stroke (mean 3.65, CI 3.58-3.73) was also associated with the greatest reduction in positive well-being whereas diabetes (mean 3.81, CI 3.76-3.86) and cancer were least affected (3.85, CI 3.79-3.91), compared with no illness (mean 3.97, CI 3.95-4.00). Depression was significantly elevated in all conditions, but was most common in chronic lung disease (OR 3.04, CI 2.56-3.61), with more modest elevations in those with osteoarthritis (OR 2.08, CI 1.84-2.34) or cancer (OR 2.07, CI 1.69-2.54). Multiple co-morbidities were associated with greater decrements in QOL and affective well-being. Conclusion The presence of chronic illness is associated with impairments in broader aspects of QOL and affective well-being, but different conditions vary in their impact. Further longitudinal work is needed to establish the temporal links between chronic illness and impairments in QOL and affective well-being.